Connectedness Between Music Tokens and Major Asset Classes: Implications for Hedging and Investments Strategies - Ritesh Patel; Muhammad Zubair Chishti; Sun-Yong Choi (American Business Review)
This study examines the dynamic connectedness between four music tokens, that is, Audius, CEEK, ROCKI and Viberate and major asset classes, namely, equity, bond, crude oil, Gold, Bitcoin and USD. We used daily data from December 23, 2020, to August 30, 2024. We measure the connectedness using the quantile VAR method and the wavelet quantile correlation approach. The quantile VAR method reveals that assets play receiver and transmitter roles. However, the assets hold a weak relationship, indicating the opportunity for portfolio diversification. Further, the results of wavelet quantile correlation also discovered negative or no relationship among major assets, revealing the existence of the portfolio diversification opportunity. The economic, geopolitical, and other related factors partially drive the connectedness of the selected assets. We measured the portfolio performance using the minimum variance portfolio, minimum correlation portfolio, recently developed minimum connectedness portfolio, equally weighted portfolio and risk-parity portfolio techniques. The minimum variance portfolio has low Sharpe and also does not include any music token due to the risky nature of the music token. However, the minimum connectedness and minimum correlation portfolios consider the addition of music tokens to a significant level, which also improves portfolio diversification. Both equally weighted portfolios and risk-parity portfolios include the music token as an asset and also give a significant Sharpe ratio. Music token serves as a hedging tool for all major asset classes. The other assets also give the hedging benefit to music tokens. However, the inclusion of the music token in the portfolio results in an increase in volatility of major asset classes, indicating a limited degree of advantage of the music token. Our study provides important implications for investors, portfolio managers, policymakers and artists.